Multiplexed immune profiling and 3D co-culture assays to assess the individual checkpoint therapy response in head and neck squamous cell carcinoma - Schweihofer, Verena; Schulz, Daniela; Blazquez, Raquel; Brockhoff, Gero; Ettl, Tobias; Fiedler, Mathias; Heimer, Sina; Schikora, Juliane; Bauer, Richard J.; Wege, Anja Kathrin (Frontiers in Oncology, 2025)
BackgroundImmune checkpoint inhibitors (ICIs) have become an integral part of cancer therapy, but only a minority of patients experience durable responsiveness. Response rates vary greatly and are often unpredictable, highlighting the urgent need for predictive biomarkers to guide treatment decisions.MethodsWe investigated immune- and tumor-specific expression and secretion profiles in peripheral blood and tumor samples derived from patients with head and neck squamous cell carcinoma (HNSCC). We combined flow cytometry, LEGENDplex™ immune profiling, and preoperative/postoperative serum cytokine analyses to determine checkpoint molecules (e.g., PD-1, TIM-3, LAG-3), immune cell profiles, as well as key markers on tumor cells (CD44, PD-L1, MHC class I/II). In addition, a 3D co-culture model using tumor slices and autologous mononuclear cells from selected HNSCC patients were analyzed upon atezolizumab and pembrolizumab treatment.ResultsCo-expression of PD-1 and TIM-3 on a subset of CD8+ tumor-infiltrating T cells was frequently observed, alongside a pronounced infiltration of myeloid cells in the tumor microenvironment. In the peripheral blood, we detected elevated levels of soluble CD27 in patients compared to controls and distinct preoperative cytokine profiles (e.g., reduced IFN-γ, CCL3, CCL20; elevated IL-15/IL-16). Postoperatively, most cytokines showed lower levels compared to healthy controls but significantly higher CCL2 levels. Furthermore, tumor–immune co-cultures from selected patients showed a stronger apoptotic response and phenotypic differences (e.g., increased PD-1 and CD137 expression) upon atezolizumab treatment. Individual changes in soluble factor release (e.g., Gal-9, sPD-L1, sCD25, and sTIM-3) was noticeable upon co-culture under immune checkpoint therapy.ConclusionsThis study provides proof-of-principle data suggesting that a combined multiplexed marker profiling and a functional 3D co-culture assay may help to explore predictive ICI response for HNSCC patients in the future. However, extensive studies with larger cohorts are warranted to validate and refine this approach.